A SUBTITLING ANALYSIS OF TRANSACTIONAL SPEECH IN THE EAGLE EYE MOVIE - WULANDARI , SEKAR PUTRI (2011)
This research aimed at describing the variations of the subtitling strategy and describing the accuracy of the subtitling of transactional speech used in The Eagle eye movie. This research is descriptive qualitative research. In collecting the data, the writer uses documentation method. The data are transactional speech in the movie manuscript and subtitle of the Eagle Eye movie . To clarify the variations of subtitling strategies, the researcher refers to subtitling strategies theory, and to describe the accuracy of subtitling of transactional speech, the researcher applies the theory of concept of accuracy. After analyzing 52 data of transactional speech, the researcher finds that (1) from 11 strategies of subtitling, the subtitler only applies 4 strategies, namely: transfer, deletion, paraphrase, and condensation. From 52 data, there are 24 data or 46,16% belong to transfer strategy, 8 data or 15,38% belong to deletion strategy, 12 data or 23,08% belong to paraphrase strategy, and 8 data or 15,38% data belong to condensation strategy. (2) 49 data or 94,23% are translated accurately, and only 3 data or 5,77% are translated inaccurately.